2006
DOI: 10.1111/j.1547-5069.2006.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Barriers and Benefits to Physical Activity Among Outpatients in Psychiatric Rehabilitation

Abstract: Outpatients in psychiatric rehabilitation valued physical activity, but mental illness symptoms, medication sedation, weight gain, fear of unsafe conditions, fear of discrimination, and interpretations of program compliance were barriers. Confronting how attitudes and barriers specific to this population can affect activity and reframing program compliance to include the independent initiation of activity as part of improving health might help clients of mental health services to become more active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
176
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(186 citation statements)
references
References 21 publications
7
176
0
3
Order By: Relevance
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Although the available evidence base in this area is limited, a small number of studies suggest that factors specifically related to psychiatric illness, including behavioral symptoms (e.g., social anxiety, paranoia, and lack of initiative), medication effects (sedation and excessive weight gain preventing physical mobility), and lack of transportation or social support often prevent mentally ill adults from engaging in weight loss treatment. 20,21 Programming that increases health knowledge and that offers social engagement and daily structure is cited as promoting engagement in behavioral weight loss programs. 22 There have been no published reports of behavioral weight loss interventions in antipsychotic treated youth, and no data are available regarding the preferences for and barriers to participating in behavioral weight loss interventions in this uniquely at-risk population.…”
mentioning
confidence: 99%
“…In addition, group activities promote social interaction and contribute to a more enjoyable experience (Fogarty and Happell, 2005;Holley et al, 2011). One role of activity is to create and maintain supportive social relationships (McDevitt et al, 2006). Thus, being able to provide and maintain a social network within the activity setting is important for prolonged engagement.…”
Section: Maintaining Activitymentioning
confidence: 99%
“…Being able to do something that can add to or change their lifestyle and routine was highly valuable to patients with SMI. Physical benefits were also present and included the general effects of participating in activity like weight loss (Fogarty & Happell, 2005;Chiverton et al, 2007) or indeed just having knowledge of the benefits of a more healthy lifestyle (Tetlie et al, 2009;McDevitt et al, 2006). Before activity is initiated, feelings of isolation can prevent activity engagement (Hodgson et al, 2011;Roberts & Bailey, 2011).…”
Section: Initiating Activitymentioning
confidence: 99%
“…When trying to inspire service users in mental health services, it is important to make physical activity as intrinsically motivating as possible by focusing on the positive experiences of the activity itself, as well as helping to develop daily routines for physical exercise (Sörensen, 2005). Common barriers to physical activity have been identified as limited experience of physical activity engagement: the impact of the mental ill health and effects of medication, in addition to discrimination and safety concerns (Johnstone, Nicil, & Donaghy et al, 2009; McDevitt, Snyder, & Miller et al, 2006). Master’s level mental health nurses can implement strategies to make the person feel capable to achieve a healthier lifestyle, as the opposite experience could lead to a feeling of failure and result in avoidance behaviour related to physical activity (Wärdig, Bachrach-Lindström, & Lindström et al, 2015).…”
Section: Skillsmentioning
confidence: 99%